Glutamate Transporters Regulate Lesion-Induced Plasticity in the Developing Somatosensory Cortex - Takasaki, Chihiro (J Neurosci, 2008)
Glutamate transporters are involved in neural differentiation, neuronal survival, and synaptic transmission. In the present study, we examined glutamate transporter 1 (GLT1) expression in the neonatal somatosensory cortex of C57BL/6 mice, and pursued its role in somatosensory development by comparing barrel development between GLT1 knock-out and control mice. During the first few neonatal days, a critical period for barrels, GLT1 expression is strikingly upregulated in cortical astrocytes, whereas it was downregulated in neuronal elements to below the detection threshold. GLT1 knock-out neonates developed normally in terms of body growth, cortical histoarchitecture, barrel formation, and critical period termination. However, when row C whiskers were lesioned during the critical period, reduction of lesioned row C barrels and reciprocal expansion of intact row B/D barrels were both milder in GLT1 knock-out mice than in control littermates. Accordingly, the map plasticity index, calculated as (B + D)/2C, was significantly lowered in GLT1 knock-out mice. We also found that extracellular glutamate levels in the neonatal somatosensory cortex were significantly elevated in GLT1 knock-out mice. Diminished lesion-induced plasticity was further found in mutant mice lacking glutamate–aspartate transporter (GLAST), an astrocyte-specific glutamate transporter throughout development. Therefore, glutamate transporters regulate critical period plasticity by enhancing expansion of active barrels and shrinkage of inactive barrels. Because cortical contents of glutamate receptors and GLAST were unaltered in GLT1 knock-out mice, this action appears to be mediated, at least partly, by keeping the ambient glutamate level low. Considering an essential role of glutamate receptors in the formation of whisker-related thalamocortical synapse patterning, glutamate transporters thus facilitate their activity-dependent remodeling.